Photoswitching Emission with Rhodamine Spiroamides for Superresolution Fluorescence nanoscopies - Belov, Vladimir N. (2013)
Spatial resolution in far-field fluorescence microscopy is limited by diffraction to about 200 nm. With the aid of photoswitchable fluorophores, the diffraction barrier has been successfully overcome, allowing unprecedented resolution in the order of single biomolecules. The imaging process demands markers with strict and reliable control of the switching, to keep most of the markers in a non-emissive state most of the time and to bring a tiny number back to an emissive state, and detection at the single-molecule level. Herein, we describe the use of rhodamine spiroamides with unique photophysical properties as molecular probes for super-resolution techniques based on the localization of single emitters. This family of photochromic and fluorescent compounds fulfils the stringent requirements for such imaging methods; these compounds are robust and capable of enduring single-molecule detection in diverse environments. This has allowed meaningful images with resolution down to a few nanometres. Their design, synthesis and implementation is discussed along with imaging applications in material and life sciences.